2012
DOI: 10.1364/ol.37.001283
|View full text |Cite
|
Sign up to set email alerts
|

Singly resonant optical parametric oscillator based on adhesive-free-bonded periodically inverted KTiOPO_4 plates: terahertz generation by mixing a pair of idler waves

Abstract: We implemented a singly resonant optical parametric oscillator based on adhesive-free-bonded periodically inverted KTiOPO4 plates. It has major advantages such as walk-off compensation and oscillation at four wavelengths. The threshold of the oscillation was measured to be 8 MW/cm2, which is about a factor of 4 lower than that based in two separate KTiOPO4 crystals. By frequency-mixing the dual-wavelength output in GaP stacks, we generated the terahertz radiation at 2.54 THz. The tuning range of the terahertz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…A pioneering "hybrid" approach, generating far-IR radiation by mixing onto a MIM diode a frequencylocked CO 2 laser and a QCL emitting around 8-μm wavelength, allowed tunable spectroscopy of rotational lines of hydrogen bromide [109]. More recently, plenty of work has been done in order to develop high performance DFG setups [110][111][112][113][114][115][116]. However, the aforementioned setups were generally bulky and unreliable and emitted low output powers (in the nW to μW range).…”
Section: Far-ir Domainmentioning
confidence: 99%
“…A pioneering "hybrid" approach, generating far-IR radiation by mixing onto a MIM diode a frequencylocked CO 2 laser and a QCL emitting around 8-μm wavelength, allowed tunable spectroscopy of rotational lines of hydrogen bromide [109]. More recently, plenty of work has been done in order to develop high performance DFG setups [110][111][112][113][114][115][116]. However, the aforementioned setups were generally bulky and unreliable and emitted low output powers (in the nW to μW range).…”
Section: Far-ir Domainmentioning
confidence: 99%
“…In recent years, it has been demonstrated that coupled optical parametric oscillations (OPOs) can simultaneously generate two pairs of signal and idler waves from periodically-inverted KTiOPO 4 (KTP) plates by a single pump wavelength [1,2]. The wavelengths for each pair of signal and idler waves satisfy quasi-phase-matching (QPM) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Difference frequency generation (DFG) with two closely spaced laser frequencies ω 1 and ω 2 in second-order nonlinear optics crystals is one of the promising processes for efficient monochromatic THz wave output in the wide frequency tuning range and for room temperature operation [5,6]. Recently, high-efficiency THz wave generation based on DFG employing Cherenkov phase matching has been intensively researched [7][8][9].…”
Section: Introductionmentioning
confidence: 99%